Phytochemical screening and antibacterial activity of Gymnema sylvestre (Retz) R . Br ex. Schultes and Morinda pubescens J.E. Smith var. pubescens - Murugan M, Mohan V. R, Thamodharan V. (Journal of Applied Pharmaceutical Science)
Two medicinal plants namely Gymnema sylvestre and Morinda pubescens var. pubescens were screened for potential antibacterial activity against Staphylococcus aureus, Klebsiella pneumoniae, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi. The antibacterial activity was determined in petroleum ether, chloroform, acetone, methanol and aqueous extracts using disc diffusion method. The chloroform and methanol extract of leaf of Gymnema sylvestre showed highest inhibition against Escherichia coli and Klebsiella pneumoniae respectively; whereas, acetone extract of Morinda pubescens var.pubescens leaf exhibited maximum inhibition against Pseudomonas aeruginosa. Phytochemical screening revealed the presence of alkaloids, flavonoids, phenols, tannins, and terpenoids. The results of these studies revealed most valuable information and also support the continued sustainable use of these plants in traditional systems of medicine.
Keywords: Gymnema sylvestre, Morinda pubescens var. pubescens, antibacterial activity, disc diffusion method.